Phase Transformation on Interface between NiCoCrAlY Bond Coat and Substrate and Study of Thermal Barrier Coating as High Temperature Material - Purwaningsih, H; Noerochim, L.; Fajarain, R.; Hakim, J.A.; Sulistijono, Sulistijono (IPTEK The Journal for Technology and Science, 2010)
Thermal Barrier Coating material consists of Yttria stabilized zirconia (YSZ) as a top coat and bond coat NiCoCrAlY. It is used to protect NiCoCrAlY super alloys for high temperature applications due to its corrosion resistant properties and resistance to thermal fatigue. In the present study, top coat and bond coat were deposited on the substrate using plasma spraying process, followed by thermal fatigue treatment, by heating up to 900 oC for 5 hours and cooling down to 25 oC for 15 minutes, this process called one cycle. Thermal fatigue was conducted until the material failure. Electron microscope was used to analysis microstructure of the sample after thermal fatigue and x-ray diffraction to analysis phase changed on the interface between bond coat and substrate. The result showed that the specimens failed at 42 cycles (210 hours). A new phase identified as Ni3Al was formed.